Effects of electrical stimulation and hot boning on the functional characteristics of presalted beef muscle used in sausage manufacturing - Choi, Y.I.; Hunt, Melvin C.; Kropf, Donald H.; Kastner, Curtis L.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2010)
Presalted, hot-boned muscle has excellent emulsifying properties for sausage manufacturing. However, electrical stimulation degrades these properties. Thus, while electrical stimulation and hot boning produce acceptable steaks and roasts, the value of the trimmings used in manufactured meat products may be lowered. Presalting maintained the high pH values of the hot-boned muscle during 24 hours storage.
Keywords: Beef; Electrical stimulation; Hot boning; Presalted muscle